The Opera Manual - Martin, Nicholas Ivor (Rowman & Littlefield Publishers, 2013)
You are getting ready for a performance of Donizetti’s L’elisir d’amore and you have a few questions. How many clarinets are in the orchestra? How many orchestra members appear onstage? How many different sets are there? How long does the opera typically run? What are the key arias? Are any special effects or ballet choreography required? Who owns the rights? Where was it premiered? What are the leading and supporting roles? The Opera Manual is the only single source for the answers to these and other important questions. It is the ultimate companion for opera lovers, professionals, scholars, and teachers, featuring comprehensive information about, and plot summaries for, more than 550 operas—including every opera that is likely to be performed today, from standard to rediscovered contemporary works. The book is invaluable, especially for opera professionals, who will find everything they need for choosing and staging operas. But it is also a treasure for listeners. Similar reference books commonly skip over scenes and supporting characters in their plot summaries, lacking even the most basic facts about staging, orchestral, and vocal requirements. The Opera Manual, based on the actual scores of the works discussed, is the only exhaustive, up-to-date opera companion—a “recipe book” that will enable its readers to explore those operas they know and discover new ones to sample and enjoy.